Evaluation of The Effectiveness of Modular Infiltration Boxes in Reducing Surface Runoff in Urban Areas: A Case Study In Cirebon City, Indonesia - Tribhuwana, Awliya; Wahyudi, Slamet Imam; Ni’am, Moh. Faiqun Ni’am (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
The urban area of Cirebon City, Indonesia, with its tropical climate, in the Sunyaragi sub-district, is increasingly affected by surface runoff and flooding due to limited drainage capacity and extensive impervious surfaces. This study evaluates the effectiveness of a modular infiltration box system in reducing urban stormwater runoff. Hydrological data from Harjamukti, Kamun, and Kertajati stations from 2014 to 2023 were analyzed using a Log Pearson Type III distribution to determine rainfall intensity for return periods of 2, 5, and 10 years. Field Experiment and Laboratory Analysis Methods: Soil infiltration characteristics were tested using a double ring infiltrometer and modeled with the Horton infiltration equation. Infiltration boxes measuring 1.00×0.50×0.45m were installed on the road median in two configurations, single layer (22 units) and double layer (44 units). The results showed that the single-layer system reduced runoff by 43.06% for a 5-year return period (15-minute duration), while the double-layer system achieved a reduction of up to 86.60% for a 2-year return period (20-minute duration). Further improvements were observed when combined with infiltration wells, achieving runoff reductions of over 95%. These findings demonstrate that modular infiltration boxes are an effective and scalable alternative solution for decentralized urban stormwater management, contributing to flood mitigation and sustainable drainage planning.